Water Quality Analysis Seen from Macrobenthos (Gastropoda) Bioindicators in the Coastal Waters of Kotania Hamlet - Arini, Ine; Smith, Alwi; Pattiasina, Eifan Boyke (Sam Ratulangi University, 2026)
Macrobenthos is a biological resource of water that lives at the bottom of the waters with characteristics that have a high level of sensitivity to changes in environmental quality as a bioindicator of pollution and environmental quality. The purpose of this study was to determine the diversity of macrobenthos as an indicator of pollution in the coastal waters of Kotania. Descriptive research with a random sampling method with a square transect. Data collection through observation of macrobenthos populations. The results of the macrobenthos diversity study obtained were in the Gastropoda class with six families namely Cerithiidae, Neritidae, Mitridae, Nassariidae, Littorinidae and Potamididae consisting of nine species namely Cerithium coniculatum, Nerita polita, Nerita patula, Nerita alveolus, Mitra pica, Nasarius pullus, Litorina scabra, Terebralia palustris and Telescopium telescopium, which shows its role as a potential bioindicator associated with dissolved oxygen, water clarity, and higher nutrient levels, indicating its suitability as an indicator of mild to moderate pollution conditions. These findings indicate that macrozoobenthos communities respond sensitively to land use changes and can effectively indicate variations in coastal water quality